Imaging Determinants of Clinical Effectiveness of Lumbar Transforaminal Epidural Steroid Injections. Issue 12 (23rd March 2016) - Maus, Timothy P; El-Yahchouchi, Christine A; Geske, Jennifer R; Carter, Rickey E; Kaufmann, Timothy J; Wald, John T; Diehn, Felix E
Abstract : Objective. To examine associations between imaging characteristics of compressive lesions and patient outcomes after lumbar transforaminal epidural steroid injections (TFESIs) stratified by steroid formulation (solution versus suspension). Design/Subjects. Retrospective observational study, academic radiology practice. A 516-patient sample was selected from 2, 634 consecutive patients receiving lumbar TFESI for radicular pain. Methods. The advanced imaging study(s) preceding sampled TFESI were reviewed. Compressive lesions were described by a) nature of the lesion [disc herniation, fixed stenosis, synovial cyst, epidural fibrosis, no lesion] b) degree of neural compression [4 part scale], and c) presence of a tandem lesion. Associations between 2-month categorical outcomes (responder rates for pain, functional recovery) and imaging characteristics, stratified by steroid formulation, were examined with chi-squared tests of categorical outcomes and multivariable logistic regression models. Results. Disc herniation patients had more responders for functional recovery than patients with fixed lesions (54% versus 38%, P  = 0.01). Patients with fixed lesions receiving steroid solution (dexamethasone) had more responders for pain relief, with a similar trend for functional recovery, than patients receiving suspensions (59% versus 40%, P  = 0.01). Outcomes for patients with fixed lesions treated with dexamethasone were not statistically different from those for disc herniation patients. Patients with single compressive lesions had more responders than those with tandem lesions (55% versus 41%, P  = 0.03). Conclusion. In the entire sample, outcomes for disc herniations were more favorable than for fixed lesions. However, fixed lesions treated with dexamethasone had outcomes indistinguishable from disc herniations. Single lesions had better outcomes than tandem lesions.